Síntese de redes de trocadores de calor com avaliação econômica e ambiental - Mano,Thiago Bernardinelli (2015)
The importance of synthesis of Heat Exchanger Networks (HEN) is due to reduction in costs during the production phase by means of a more efficient use of energy. This is directly reflected in minimizing the amount of pollution load arising from combustion of fuels for energy generation. Moreover, impacts caused by industrial processes are now the center of attention of much research in the environmental area. Thus, given the great importance that the synthesis of HEN has in reducing the cost and impacts, in this work the goal was synthesize HENs taking into account economic and environmental assessment. Many published studies have not considered the fuel type used for generation of utilities. The main fuel present in industries are hardcoal, hardwood, heavy and light fuel oil and natural gas. A boiler that operates with each of these fuels is considered in this thesis. The method Life Cycle Assessment (LCA) was used. The eco-cost was used for the conversion of impacts in economic terms. Four models were developed. The first one uses the particle swarm algorithm adapted to multi-objective problems with binary variables and ReCiPe. The second model is similar to the first, but the eco-cost replaces the ReCiPe. Programming FUZZY-AHP is applied on the third model. The fourth model takes the multi-objective problem into a single objective problem. Results showed that the HEN cost operating with hardwood is the largest among all fuels and the lowest impact. The HEN operating with hardcoal has the lowest HEN cost and the higher impact. The HEN operating with natural gas had the lowest total cost. Finally, the results of total costs were compared. Thus, it can be concluded that the HEN operating with natural gas is the best network, as had the lowest total cost.